Economic Evaluation of Universal Varicella Vaccination in Mexico. Issue 5 (28th December 2021) - Chacon-Cruz, Enrique; Meroc, Estelle; Costa-Clemens, Sue Ann; Clemens, Ralf; Verstraeten, Thomas
Abstract : Background: Universal varicella vaccination has proven to be cost-effective (CE) in countries where implemented. However, this has not been evaluated for Mexico. Methods: The yearly disease burden (varicella cases/deaths, outpatient visits, and hospitalizations) was derived from Mexican seroprevalence data adjusted to the 2020 population. The yearly economic burden was calculated by combining disease with Mexican unit cost data from both health care and societal perspectives. Four different vaccination strategies were evaluated: (1) 1 dose of varicella vaccine at 1 year old; (2) 2 doses at 1 and 6 years; (3) 1 dose of varicella vaccine at 1 year, and quadrivalent measles-mumps-rubella-varicella vaccine at 6 years; (4) 2 doses of measles-mumps-rubella-varicella vaccine at 1 and 6 years. We developed an economic model for each vaccination strategy where 20 consecutive birth cohorts were simulated. Vaccination impact (number of avoided cases/deaths) was evaluated for a 20-year follow-up period based on vaccine effectiveness (87% and 97.4% for 1 and 2 doses), and assuming a 95% coverage. We estimated annual costs saved, incremental cost-effectiveness ratio, and costs per life year gained. Results: Avoided cases during the 20-year follow-up with 1, and 2 doses were 20, 570, 722 and 23, 029, 751, respectively. Strategies 1 and 2 were found to be cost saving, and strategy 3 to be CE. Strategy 4 was not CE. Strategies 1 and 2 would allow saving annually 53.16 and 34.41 million USD, respectively, to the Mexican society. Conclusions: Universal varicella vaccination, using 1 dose or 2 doses, would result in a cost-beneficial and CE public health intervention in Mexico.